Tutorial: Computing Topological Invariants in 2D Photonic Crystals. Issue 2 (19th December 2019) - Blanco de Paz, María; Devescovi, Chiara; Giedke, Geza; Saenz, Juan José; Vergniory, Maia G.; Bradlyn, Barry; Bercioux, Dario; García‐Etxarri, Aitzol
Abstract: The field of topological photonics emerged as one of the most promising areas for applications in transformative technologies: possible applications are in topological lasers or quantum optics interfaces. Nevertheless, efficient and simple methods for diagnosing the topology of optical systems remain elusive for an important part of the community. Herein, a summary of numerical methods to calculate topological invariants emerging from the propagation of light in photonic crystals is provided. The fundamental properties of wave propagation in lattices with a space‐dependent periodic electric permittivity is first described. Next, an introduction to topological invariants is provided, proposing an optimal strategy to calculate them through the numerical evaluation of Maxwell's equation in a discretized reciprocal space. Finally, the tutorial is complemented with a few practical examples of photonic crystal systems showing different topological properties, such as photonic valley‐Chern insulators, photonic crystals presenting an "obstructed atomic limit", photonic systems supporting fragile topology, and finally photonic Chern insulators, where the magnetic permeability is also periodically modulated. Abstract : Herein, the principal properties of photonic crystals in two‐dimensions are introduced. Additionally, it provides a step by step explanation as to how to compute topological invariants in a discretized reciprocal space. The methods presented are applied to several photonic crystal examples, including valley‐Chern insulators, photonic "obstructed atomic limit" insulators, fragile topological insulators, and Chern insulators.